Hotel Ayllu: la aventura ancestral del Valle Sagrado - Paredes Tupiño, Luis Alfredo (2023)
In the midst of a sector that still has not recovered from the ravages and great economic losses caused by the pandemic and is also on the verge of bankruptcy (Diario Gestión, 2023) due to the constant social upheavals that have occurred in the last two years, the company A-Experience seeks to impact a prestigious public with a new proposal in sustainable luxury hotels, this time in Urubamba with the launch of the Ayllu Experience Urubamba Hotel. This new and luxurious option invites guests to disconnect from the noise of the city and explore all the secrets of the Incas in the middle of an ancestral valley. During the resolution of the case, we will generate a launch strategy that differentiates from the experienced local competition and achieve 80% guest occupancy by the end of the first year of operations. With the support of primary and secondary sources collected during the development of the proposal, the launch plan for Hotel Ayllu Experience Urubamba was elaborated with a communication approach based on the digital and radio segment, where a brandbook and base concept for the brand, a strategy focused on PR, written, radio and digital press and, finally, a budget breakdown were presented.